Laser ultrasonic testing of defects in milling groove brazed joints of thrust chamber - Chen, Yuhang; Kou, Xing; Liu, Yu; Pei, Cuixiang; Chen, Zhenmao (Frontiers in Materials, 2024)
This paper presented a new approach for noncontact inspection of defects in milling groove brazed joints of thrust chamber with laser ultrasonic testing method and synthetic aperture focusing technique (SAFT). Firstly, laser ultrasonic testing methods for milling groove brazed joints of thrust chamber was studied. Subsequently, numerical models were constructed to analyze the influence of defects on laser-excited signals. The analysis revealed that the brazed defects caused internal waves to reflect on the rib surface, manifesting as defect echo signals preceding the outer wall echo. Through scanning setting, the obtained SAFT images illustrate the presence of the defect directly and clearly. Furthermore, an experimental system was established to detect and image artificial defects with different degrees of weld leakage. The experimental results are consistent with simulation results, validating the capability and effectiveness of the testing and imaging method. In general, the proposed laser ultrasound method offers inherent advantages of non-contact detection with high resolution and precision, and it is easy to achieve fast and automated scanning of large and complex structures like thrust chambers, demonstrating its potential for enhancing the safety and reliability of liquid rocket engines.